Effect of Different Feeding Regimes on Feed Intake, Body Weight and Body Condition Score of Crossbred Cows - Islam, Md. Manzarul; Shah, Shailesh V.; Pandya, Paresh R.; Lunagariya, Pravin M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted from 45 d prepartum to 300 d post-partum on 18 crossbred cows, distributed into three treatment groups comprising six animals in each group. Animals of the T1 (Farmers’ feeding) group were maintained as per the feeding regime, followed by small and marginal farmers. Animals of T2 (Modified feeding)group were fed with scientific interventions using resources available with farmers. Animals of the T3 (Farm feeding) group were fed as per feeding followed at Livestock Research Station. Average DMI both on kg/ animal/d and kg/100 kg b.wt. was significantly (p <0.05) higher in T2 (12.45 ± 0.28 and 2.74 ± 0.06) and T3 (12.62 ± 0.22 and 2.81 ± 0.06) as compared to T1 (9.71 ± 0.20 and 2.24 ± 0.05, respectively) group. Similarly, average DCPI (g/animal/d) was significantly (p <0.05) higher in T2 (801.87 ± 22.30) and T3 (839.53 ± 16.63) when compared with T1 (543.83 ± 14.83) group. Average DCPI (g/100 kg b.wt.) was 128.49 ± 4.51, 177.40 ± 5.00, and 187.84 ± 4.51 in T1, T2, and T3 groups, respectively, which differed significantly (p <0.05) among each other. Average TDNI both on kg/animal/d and kg/100 kg b.wt. was significantly (p <0.05) higher in T2 (7.13 ± 0.16 and 1.57 ± 0.04) and T3 (7.30 ± 0.13 and 1.63 ± 0.04) as compared to T1 (4.82 ± 0.10 and 1.11 ± 0.03, respectively) group. Irrespective of periods, the overall body weight (kg) of crossbred cows were significantly (p <0.05) higher in the T2 (459.32 ± 5.69) and T3 (458.55 ± 5.72) as compared to the T1 (444.58 ± 6.41) group of animals. The average body condition score was maximum in T3 (3.29 ± 0.02) followed by T2 (3.07 ± 0.03) and T1 (2.89 ± 0.03) groups, which differed significantly (p <0.05). It may be concluded from the present study that the feeding regime significantly influenced feed intake, body weight, and body condition score of crossbred cows.